Mobile Augmented Reality Application: Understanding Covid-19 - Shaparudin, Amiruddin Hakim; Din, Suhaili (Journal of Computing Technologies and Creative Content, 2021)
Augmented Reality (AR) is a technology in which a computer-generated image is superimposed onto the user’s vision of the real world, giving the user additional information generated from the computer model. AR can present information just in time, in situation when people need it. It is very clear, and it allows you to communicate sometimes, pretty technical and complicated things very effectively. As our society today is not fully aware on the dangerous of this virus, this system is a helpful platform. The aim of this research is to educate and spread awareness about the new diseases Covid-19 that has been rampages all around the world. In line with that, the objective of this application is to make it easier for people to understand precisely about Covid-19 on how it spreads and running through human’s body. In this situation, the learning potential of AR is significantly amplified by the capability of the system to present 3D models in real-time at remote locations.